Spatial variations of 226Ra, 228Ra, 134Cs, and 137Cs concentrations in western and southern waters off the Korean Peninsula in July 2014. (February 2018) - Inoue, M.; Shirotani, Y.; Nagao, S.; Aramaki, T.; Kim, Y.I.; Hayakawa, K.
Abstract: We examined the spatial distributions of 226 Ra, 228 Ra, 134 Cs, and 137 Cs concentrations (activities) in seawater off the western and southern Korean Peninsula in July 2014. Radium-228 (and 226 Ra) concentrations in water samples varied widely from 5 to 14 mBq/L (2–4 mBq/L), showing a negative correlation with salinity, particularly at the surface off the western Korean Peninsula. This indicates that the seawaters in this area are fundamentally comprised of 228 Ra-poor and high-saline Kuroshio Current water and 228 Ra-rich and low-saline water (e.g., continental shelf water), with various mixing ratios. Although Fukushima Dai-ichi Nuclear Power Plant (FDNPP)-derived 134 Cs was below the detection limit (<0.08 mBq/L) in waters off the western Korean Peninsula, low level 134 Cs (0.1–0.2 mBq/L) was detected in waters off the southern Korean Peninsula accompanied by higher 137 Cs concentrations (1.6–1.9 mBq/L) relative to that off the western Korean Peninsula. Combined with the lower radium concentrations, the detection of 134 Cs is explained by mixing of FDNPP-derived radiocesium-contaminated Kuroshio Current water. Highlights: We determined radium and radiocesium in seawater around the Korean Peninsula in 2014. Radium concentrations were governed by the mixing ratio of Kuroshio Current water. 134 Cs (0.1–0.2 mBq/L) was detected at the surface of the southern Korean Peninsula. 134 Cs level was negligible due to the low concentration in the Kuroshio Current.